Subject Liaisons in Academic Libraries: An Open Access Data Set from 2015 - Nero, Neil; Langley, Anne (Portal (Baltimore, Md.), 2017)
The work of subject liaison librarians in academic libraries has morphed to include a variety of roles that reach beyond the traditional. This study captures responses of 1,808 participants from land-grant, Oberlin Group, and Association of Research Libraries (ARL) institutions to a questionnaire about subject liaison librarians. The questionnaire contains eight demographic questions, five questions about liaison responsibilities, seven outreach and instruction questions, three traditional reference questions, two scholarly communications questions, three collection development questions, and an open-ended question. This is the largest data set compiled to date on academic subject liaison librarians. The data set has been made available on an open access basis in hopes that use of the data will facilitate cross-study comparisons.